Farmer Participatory Assessment of Integrated Pest Management Strategies against the Insect Pest of Lowland Rice in Coastal Odisha - Nayak, U. S.; Das, A.; G, Shial (International Journal of Bio-resource and Stress Management, 2019)
On-farm testing was conducted at farmers’ field to assess the efficacy of IPM technology against the major insect pest of lowland rice during kharif 2010 and 2011. IPM module I comprising of nursery treatment with Carbofuron 3G @ 120 g/1 cent nursery area, release of bioagent Trichogramma chilonis @ 0.1 million ha-1 4 times at 10 days interval, foliar spraying of neem oil @ 1.5 l ha-1 at 45 and 75 DAT and fipronil 5 SC @ 1 l ha-1 at 60 DAT, rope dragging for dislodging pest in kerosinised water and need based spraying of Ethofenprox 10 EC @ 500 ml ha-1 at 90 DAT recorded the lowest yellow stem borer infestation (4.55% mean dead heart, 3.81% mean white ear head), leaf folder damage (7.29% mean leaf damage), case worm incidence (11.50% mean leaf damage) and plant hopper incidence (8.27 mean population/hill) and was found to be significantly superior to the farmers’ practice of indiscriminate application of 4 to 5 insecticides. A significantly higher natural enemy (spiders and mired bugs) population was retained in both the IPM modules. The highest mean grain yield (45.9 q ha-1), net rerun (Rs. 18780.00) and B:C ratio (1.65) was obtained from the IPM module I justifying the economic superiority of this IPM module